THE Practice of Human Rights Tracking Law Between the Global and the Local - Goodale, Mark (Cambridge University Press, 2013)
In January 2002 Fiji presented its first ever country report to the United Nations committee charged with monitoring compliance with the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). One of the most controversial sections of the report addressed the use of the practice of bulubulu, or village reconciliation, in cases of rape